Impact of the COVID-19 pandemic on cardiovascular mortality and contrast analysis within subgroups - Song, Shoufang; Guo, Chen; Wu, Ruiyun; Zhao, Hong; Li, Qiang; Dou, Jia-hao; Guo, Fan-shun; Wei, Jin (Frontiers in Cardiovascular Medicine, 2024)
Background An increase in deaths has been perceived during the pandemic, which cannot be explained only by COVID-19. The actual number of deaths far exceeds the recorded data on deaths directly related to SARS-CoV-2 infection. Data from early and short-lived pandemic studies show a dramatic shift in cardiovascular mortality. Grounded in the post-pandemic era, macroscopic big data on cardiovascular mortality during the pandemic need to be further reviewed and studied, which is crucial for cardiovascular disease prevention and control. Methods We retrieved and collected data associated with cardiovascular disease mortality from the National Vital Statistic System from the Center for Disease Control and Prevention Wide-Ranging Online Data for Epidemiologic Research (CDC WONDER) platform based on the ICD-10 codes. We applied regression analysis to characterize overall cardiovascular disease mortality trends from 2010 to 2023 and built a time series model to predict mortality for 2020–2023 based on mortality data from 2010 to 2019 in order to affirm the existence of the excess deaths by evaluating observed vs. predicted mortality. We also conducted subgroup analyses by sex, age and race/ethnicity for the purpose of obtaining more specific sociodemographic information. Results All-cause age-standardised mortality rates (ASMRs) for CVD dramatically increased between 2019 and 2021[annual percentage change (APC) 11.27%, p < 0.01], and then decreased in the following 2021–2023(APC: −7.0%, p < 0.01). Subgroup analyses found that the ASMR change was most pronounced in Alaska Indians/Native American people (APC: 16.5% in 2019–2021, −12.5% in 2021–2023, both p < 0.01), Hispanics (APC: 12.1% in 2019–2021, −12.2% in 2021–2023, both p < 0.05) and non-Hispanic Black people (APC:11.8% in 2019–2021, −10.3% in 2021–2023, both p < 0.01)whether during the increasing or declining phase. Similarly, the ASMR change was particularly dramatic for the 25–44 age group (APC:19.8% in 2019–2021, −15.4% in 2021–2023, both p < 0.01) and males (APC: 11.5% in 2019–2021, −7.6% in 2021–2023, both p < 0.01). By the end of 2023, the proportion of COVID-related excess death remained high among the elderly (22.4%), males (42.8%) and Alaska Indians/Native American people(39.7%). In addition, we did not find the presence of excess deaths in the young (25–44) and middle-aged cohort (45–64) in 2023, while excess deaths remained persistent in the elderly. Conclusions All-cause ASMRs for CVD increased notably during the initial two years of the COVID-19 pandemic and then witnessed a decline in 2021–2023. The cohorts (the young, males and minorities) with the steepest rise in mortality decreased at the fastest rate instead. Previous initiatives to promote cardiovascular health were effective, but further research on cardiovascular healthcare for the elderly and racial disparities should be attached to priority considering the presence of sociodemographic differences in CVD death.